2010
DOI: 10.1007/s11606-010-1572-x
|View full text |Cite
|
Sign up to set email alerts
|

Setting a Fair Performance Standard for Physicians’ Quality of Patient Care

Abstract: BACKGROUND: Assessing physicians' clinical performance using statistically sound, evidence-based measures is challenging. Little research has focused on methodological approaches to setting performance standards to which physicians are being held accountable. OBJECTIVE: Determine if a rigorous approach for setting an objective, credible standard of minimally-acceptable performance could be used for practicing physicians caring for diabetic patients. DESIGN: Retrospective cohort study. PARTICIPANTS: Nine hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…The methodology has been previously described [9][10][11] and patented. 16 For each measure, we established a threshold for delivering both competent and excellent care using an expert panel and an adaptation of the Angoff standard-setting method.…”
Section: Composite and Standard-setting Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology has been previously described [9][10][11] and patented. 16 For each measure, we established a threshold for delivering both competent and excellent care using an expert panel and an adaptation of the Angoff standard-setting method.…”
Section: Composite and Standard-setting Methodologymentioning
confidence: 99%
“…2,6 Recent research on composites drawn from evidence-based measures has advanced the science of quality assessment. [7][8][9][10][11] Composites are comprehensive measure sets that provide a more reliable assessment than individual measures alone. 8,9 Using a composite to make a judgment about an individual physician's performance in practice requires a defensible absolute standard of performance on the composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one component of MOC, the examination serves as an objective measure of cognitive expertise. 12,13 We previously demonstrated that family physicians who are international medical graduates (IMGs), are in solo practice, or who practice in poor areas of the country are less likely to meet their MOC requirements, which includes passing the MOC examination.…”
mentioning
confidence: 99%
“…Methods to ensure safe and effective practitioners have traditionally focused on training and assessment of competence before entering practice. However, an increasing number of visionary credentialing bodies such as the American Board of Internal Medicine have created systematic methods of measuring a practitioner's ability to deliver care in practice 2 .…”
mentioning
confidence: 99%